2014
DOI: 10.1364/josab.31.001330
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of self-Kerr nonlinearity via electromagnetically induced transparency in a five-level cascade system: an analytical approach

Abstract: We propose to use a five-level cascade system to enhance self-Kerr nonlinearity under an electromagnetically induced transparency (EIT) condition. Using density-matrix theory, an expression of the self-Kerr nonlinear coefficient for a weak probe light is derived. Variations of the self-Kerr coefficient with respect to the frequency and intensity of a strong coupling light are investigated. The Kerr nonlinearity is basically modified and enhanced greatly in the spectral regions corresponding to EIT transparent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
45
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 20 publications
2
45
1
Order By: Relevance
“…Electromagnetically induced transparency also has many notable applications in quantum and nonlinear optics such as multiwave mixing [8][9][10], optical bistability [11,12], optical solitons [13][14][15][16][17], and Kerr nonlinearity [18]. Many proposals have been suggested both theoretically and experimentally for achieving enhanced Kerr nonlinearity accompanied by negligible absorption in three-and four-level atomic systems [19][20][21][22][23][24][25][26]. Wang et al [19] studied experimentally the enhanced Kerr nonlinear coefficient in a three-level -type atomic system for various powers of the coupling beam.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electromagnetically induced transparency also has many notable applications in quantum and nonlinear optics such as multiwave mixing [8][9][10], optical bistability [11,12], optical solitons [13][14][15][16][17], and Kerr nonlinearity [18]. Many proposals have been suggested both theoretically and experimentally for achieving enhanced Kerr nonlinearity accompanied by negligible absorption in three-and four-level atomic systems [19][20][21][22][23][24][25][26]. Wang et al [19] studied experimentally the enhanced Kerr nonlinear coefficient in a three-level -type atomic system for various powers of the coupling beam.…”
Section: Introductionmentioning
confidence: 99%
“…All of these studies have dealt with the three-and four-level atomic systems. More recently, Khoa et al [26] investigated theoretically the possibility of obtaining an enhanced self-Kerr-nonlinearity under the EIT condition for a five-level cascade system. They also made a comparison between the behavior of self-Kerrnonlinearity for such a five-level atomic system with that of four-and three-level cascade systems and observed the same magnitude of the self-Kerr-nonlinear coefficient among the three systems.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of EIT [4] offers coherent media of vanished resonant absorption [5][6][7][8] and controllable giant Kerr nonlinearity [9][10][11]. Wang et al performed a direct measurement of self-Kerr nonlinear coefficient in a three-level lambda EIT medium in the presence of Doppler broadening by using a cavity scanning technique.…”
Section: Introductionmentioning
confidence: 99%
“…In nonlinear optics, due to significant role of Kerr nonlinearity in some important phenomena [26,27], it is favoraitable to have giant Kerr nonlinearity in low light intensities [28]. Recently it has been shown that the giant enhanced Kerr nonlinearity in multi-level atomic systems with zero linear absorption can be possible by different mechanisms [29][30][31][32][33][34][35][36][37][38]. Niu et al investigated giant Kerr nonlinearity via double dark resonances in a four-level atomic system [35].…”
Section: Introductionmentioning
confidence: 99%